2013
DOI: 10.1007/s11357-013-9512-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the WRN gene and DNA damage of peripheral lymphocytes in age-related cataract in a Han Chinese population

Abstract: Werner syndrome is caused by mutations in the DNA repair Werner helicase (WRN) gene and characterized by accelerated aging including cataracts. Age-related cataract (ARC) cases (N = 504) and controls (N = 244) were recruited from a population-based study to evaluate the association of single-nucleotide polymorphisms (SNPs) of WRN and another DNA repair gene (human 8-oxoguanine DNA N-glycosylase 1) with ARC. Among the five SNPs tested, only WRN rs1346044 was found to be significantly associated between cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…The modified comet assay for lymphocytes and LECs was carried out according to the method described by Jiang et al [13], which was based on that initially reported by Singh et al [26]. The freshly prepared cell suspension of lymphocytes or LECs (1 × 10 4 cells) in 50 μl PBS mixed with 100 μl 0.75% low-melting-point agarose in PBS was spread onto slides precoated with 0.75% normal-melting-point agarose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified comet assay for lymphocytes and LECs was carried out according to the method described by Jiang et al [13], which was based on that initially reported by Singh et al [26]. The freshly prepared cell suspension of lymphocytes or LECs (1 × 10 4 cells) in 50 μl PBS mixed with 100 μl 0.75% low-melting-point agarose in PBS was spread onto slides precoated with 0.75% normal-melting-point agarose.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have detected DNA damage of peripheral lymphocytes by comet assay in ARC patients from a population-based study. We found that DNA damage of peripheral lymphocytes was significantly higher in ARC patients and associated with DNA repair gene polymorphisms [11,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Both CNVs and single nucleotide variants in WRN have been associated with age-related cortical cataract in Han Chinese. [58][59][60] In addition to genes involved in hereditary cataract, variations in other candidate genes not directly associated with inherited forms of cataract have been tentatively implicated in agerelated cataract. These include genes that function in antioxidant metabolism (GSTM1, GSTT1), lactose metabolism (LCT), drug metabolism (NAT2), folate metabolism (MTHFR), DNA repair (XPD), lipid/cholesterol transport (APOE), kinesin/microtubule motor transport (KLC1), actin-cytoskeleton regulation (EZR), chaperone activity (HSP70), and ephrin signaling (EFNA5).…”
Section: Genes Associated With Age-related Cataractmentioning
confidence: 99%
“…Investigation of WRN, including mutations, deletions and polymorphisms, are performed in a number of tumors and age-related diseases (5). The WRN codon 1367, located in the short arm of chromosome 8, is a single-nucleotide polymorphism (SNP) site (rs1346044), where the allele A-to-G change leads to a cysteine-to-arginine substitution in the WRN protein (5,6). Studies on the WRN Cys1367Arg reported an association with several diseases, such as cataract (6) and bone and soft tissue sarcomas (7); however, to the best of our knowledge, there has been no such investigation for chordoma.…”
Section: Introductionmentioning
confidence: 99%